AB0336 Magnetic resonance imaging-assessed synovial and bone changes in hand and wrist joints of rheumatoid arthritis patients. (15th June 2017) - Lee, KA; Min, S-H; Kim, T-H; Lee, S-H; Kim, H-R
Abstract : Background: Magnetic resonance imaging (MRI) is a sensitive and useful method for the detection of synovitis and joint destruction in rheumatoid arthritis (RA) patients. However, the patterns of MRI-detected bone erosion, bone marrow edema (BME), synovitis, and tenosynovitis have received insufficient attention. Objectives: Therefore, this study evaluated the patterns of bone erosion, BME, synovitis, and tenosynovitis, and calculated the RA-MRI score (RAMRIS) of patients with RA at the carpal and metacarpophalangeal (MCP) joints using MRI. Methods: MRI datasets from 43 RA patients were analyzed. All patients had undergone MRI of one wrist. In addition, 36 patients had MCP joint images taken, and 3 had also received MRI of the contralateral wrist and MCP joints. The MR images were evaluated for bone erosion, BME, and synovitis in consensus by 2 blinded readers according to the OMERACT RA-MRI score (RAMRIS). The MRI-detected tenosynovitis was evaluated based on Haavardsholm's tenosynovitis score. Results: The capitate, lunate, triquetrum, and hamate bones were the most common sites of erosion and BME and showed the highest RAMRIS erosion and BME scores. Moreover, MRI-detected tenosynovitis was present in 78.3% of all patients with RA, and the extensor compartment 4 and flexor digitorum profundus and superficialis were frequently affected. Conclusions: This study identified the distribution and prevalence of MRI-detected bone erosion, BME, synovitis, and tenosynovitis of the wrist and MCP joints in RA patients. The patterns of the MRI-detected abnormalities may help to select sites for the application of MRI protocols in clinical trials and practice. References: Ejbjerg B, McQueen F, Lassere M, Haavardsholm E, Conaghan P, O'Connor P, et al. The EULAR-OMERACT rheumatoid arthritis MRI reference image atlas: the wrist joint. Annals of the rheumatic diseases. 2005;64 Suppl 1:i23–47. Ostergaard M, Edmonds J, McQueen F, Peterfy C, Lassere M, Ejbjerg B, et al. An introduction to the EULAR-OMERACT rheumatoid arthritis MRI reference image atlas. Annals of the rheumatic diseases. 2005;64 Suppl 1:i3–7. Conaghan P, Bird P, Ejbjerg B, O'Connor P, Peterfy C, McQueen F, et al. The EULAR-OMERACT rheumatoid arthritis MRI reference image atlas: the metacarpophalangeal joints. Annals of the rheumatic diseases. 2005;64 Suppl 1:i11–21. Haavardsholm EA, Ostergaard M, Ejbjerg BJ, Kvan NP, Kvien TK. Introduction of a novel magnetic resonance imaging tenosynovitis score for rheumatoid arthritis: reliability in a multireader longitudinal study. Annals of the rheumatic diseases. 2007;66(9):1216–20. Acknowledgements: The author(s) declared no potential conflicts of interest with respect to the research, authorship, and/or publication of this article. Disclosure of Interest: None declared